Identification and Characterization of PLATZ Transcription Factors in Wheat - Fu, Yuxin (Int J Mol Sci, 2020)
The PLATZ (plant AT-rich protein and zinc-binding protein) transcription factor family is a class of plant-specific zinc-dependent DNA-binding proteins. PLATZ has essential roles in seed endosperm development, as well as promoting cell proliferation duration in the earlier stages of the crops. In the present study, 62 TaPLATZ genes were identified from the wheat genome, and they were unequally distributed on 15 chromosomes. According to the phylogenetic analysis, 62 TaPLATZ genes were classified into six groups, including two groups that were unique in wheat. Members in the same groups shared similar exon-intron structures. The polyploidization, together with genome duplication of wheat, plays a crucial role in the expansion of the TaPLATZs family. Transcriptome data indicated a distinct divergence expression pattern of TaPLATZ genes that could be clustered into four modules. The TaPLATZs in Module b possessed a seed-specific expression pattern and displayed obvious high expression in the earlier development stage of seeds. Subcellular localization data of TaPLATZs suggesting that they likely perform a function as a conventional transcription factor. This study provides insight into understanding the structure divergence, evolutionary features, expression profiles, and potential function of PLATZ in wheat.